Best Answer

With each new term, you add a number n. This number is always odd, and increases by 2 with each term. So, starting with the first term, 2, you add n = 1 to get 3; add 3 to n = 3 to get 6; add 6 to 5 to get 11; and 7 to 11 to get 18.

Here is the pattern written out:

2 + 1 = 3

3 + 3 = 6

6 + 5 = 11

11 + 7 = 18

...

Q: What is the rule to the pattern 2 3 6 11 18?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

1, 3, 4, 7, 11, 18, 29, 47

One rule for this pattern is to add twice the previous value added 4 + 1 = 5 5 + 2×1 = 5 + 2 = 7 7 + 2×2 = 7 + 4 = 11 11 + 2×4 = 11 + 8 = 19 Continuing the next numbers would be: 19 + 2×8 = 19 + 16 = 35 35 + 2×16 = 35 + 32 = 67 ...

multiply 11, subtract 10

It is not a rule as such; those number are the first 10 prime numbers.

The rule for the pattern is y=x+2. That rule is in the table format in which it would originally be in, but the worded rule would be 'It increases by 2 each time'.

Related questions

The pattern will be +2, +3, +4, +4

prime numbers

4*2-2=6 6*2-2=10

3 4 6 9 13 18...1....2....3....4......5

1, 3, 4, 7, 11, 18, 29, 47

t(n) = 3(-n2 + 6n - 2) for n = 1, 2, 3 etc

There are many possibilities. One is: Un = (8n3 - 39n2 + 79n - 36)/6 for n = 1, 2, 3, ...

It is: 3 6 12 24 48 .... double up each time

One rule for this pattern is to add twice the previous value added 4 + 1 = 5 5 + 2×1 = 5 + 2 = 7 7 + 2×2 = 7 + 4 = 11 11 + 2×4 = 11 + 8 = 19 Continuing the next numbers would be: 19 + 2×8 = 19 + 16 = 35 35 + 2×16 = 35 + 32 = 67 ...

add 6, subtract 2

multiply 11, subtract 10

The difference doubles each time. 2+3=5.. 5+6=11.. 11+12=23..Therefore the next number in the sequence would be 47, since 23+24 = 47.